Egy nyugalmazott címzetes rendkívüli egyetemi tanár baráti és tanítványi köre - Vincze, Tamás (Gerundium, 2015)
A HONORARY PROFESSOR EMERITUS AMONG HIS ACADEMIC FRIENDS AND STUDENTS. he study reviews the friendships of Ferenc Zsigmond, the private university teacher endowed with the honorary professor emeritus title in the last 15 years of his life. Zsigmond gave lectures until 1934 in Debrecen, then he lived in his birth village until his suicide in 1949. he reclusive scientist sufering from depression, kept up with scientiic developments through his friends and correspondents who played a signiicant role in his life. hese friendships meant a retention force for him, diverted his attention from his illness and postponed its progression. It is not surprising that his illness had turned really serious when he left the capital and moved to his birth village, Kunhegyes, where his regular correspondence ended and the lack of professional discourses weakened the oversensitive scientist.